2021
DOI: 10.1177/23477989211032474
|View full text |Cite
|
Sign up to set email alerts
|

Does Demographic Characteristics Affect Remittance Behavior? An Analysis of Migrants in the UAE

Abstract: The United Arab Emirates (UAE) is a popular destination for migrant workers worldwide, not just from Asia. Along with expanding the UAE’s economic activities, the amount of remittance outflows has increased dramatically, making it the second-largest remitting country, just behind the United States. This study looks into the important demographic factors that influence migrant remittance behavior in the Emirates. The examinations revealed that age, race, marital status, and a number of dependents are the most i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Building upon the literature review pertaining to our last variable of interest, namely the presence of employers in recipient countries and their impact on the outflow of remittances. In their study on the UAE, Khan and Akhtar (2021) have identified unemployment within individuals' home countries as a significant factor driving migration to the UAE. The study additionally posited that the availability of numerous employment opportunities in the host nations has a favourable impact on individuals' income and exhibits a direct relationship with the outflow of remittances from the country.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Building upon the literature review pertaining to our last variable of interest, namely the presence of employers in recipient countries and their impact on the outflow of remittances. In their study on the UAE, Khan and Akhtar (2021) have identified unemployment within individuals' home countries as a significant factor driving migration to the UAE. The study additionally posited that the availability of numerous employment opportunities in the host nations has a favourable impact on individuals' income and exhibits a direct relationship with the outflow of remittances from the country.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This article is not the first to study the characteristics of migrants who remit. Recently, Khan and Akhtar (2021) studied the demographic characteristics that affect remittance behaviours in the United Arab Emirates. This article differs from this literature by using the characteristics of a remitter, not as an end in itself.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some scholars have helped develop the literature by considering how external remittances have affected the sending countries’ macroeconomic factors and economic growth (Jena & Sethi, 2020; Naufal & Genc, 2018). Previous examinations in the area have also studied the impact of demographic characteristics on remittance behavior in the UAE (Khan & Akhtar, 2021). Even during the pandemic, the remittance outflows remained resilient to the economic slowdown caused by the virus and even registered growth in certain regions (World Bank, 2021).…”
Section: Introductionmentioning
confidence: 99%